(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article analyzes the peculiarities of public procurement in Ukraine and their role in the public finance system; the factors affecting their effectiveness are investigated; identified problems that exist in Ukraine during tender procurement, as well as difficulties in the activities of the country’s controlling structures in the field of public procurement. The purpose of the article is to reveal the peculiarities and problems of public procurement in Ukraine and to identify ways to overcome them, which, accordingly, will have a positive effect on the functioning of public finances in our country. The objectives of the article are to substantiate the directions of reforming the mechanism of public procurement in Ukraine, taking into account the experience of the EU countries; identification of financial features of public procurement after the entry into force of the new version of the Law of Ukraine "On Public Procurement"; study of forms of financial responsibility of public procurement participants in Ukraine and their effectiveness. Public procurement is a powerful tool for regulating supply and demand for specific types of products, as they represent the purchase of goods, works and services with public funds. Due to this, it is important to achieve effective use of budget funds allocated for public procurement in Ukraine, which has not yet been achieved. Therefore, in order to increase the transparency and efficiency of the use of these funds in our country, it is advisable to study the experience of the EU member states in this matter, since the main task of reforming the sphere of public procurement in our country is the implementation of an effective procurement system in accordance with the principles and approaches used by the countries of the European Union, which must ensure financial efficiency and transparency of the procurement procedure. It is also necessary to analyze the effectiveness of the changes that have taken place in the implementation of public procurement after the introduction in 2022 of the new conditions for their implementation, caused by the war of Russia against Ukraine, because along with the positive moments, there are also negative ones, which is manifested in the existence of corruption schemes during the conduct of tenders.